“BeDiL” Learning Media Training in The New Normality Era - Yohanna Nirmalasari; Dhatu Sitaresmi; Vincentius Valiandy Jiuangga (Journal of Community Practice and Social Welfare, 2021)
Online learning is a new phenomenon for educators. This requires education actors, such as educators, education staff, governments, students, and even parents of students to be able to work together in building interactive learning. Online learning is a learning method/way that can motivate students to learn more and achieve learning objectives. However, not all educators can adapt quickly, especially for educators who work in the field at the front lines. This can happen because, over the years, educators have been accustomed to face-to-face or offline teaching models instead of a virtually face-to-face or online model. When learning is carried out online, this becomes a challenge for educators where they have to learn many new things such as the media platforms, new presentation methods, or adapted teaching strategies so that learning can be done effectively. Moreover, an educator is a wheel in learning. Therefore, training on the design of a learning media, especially in the face of this new normal era, is crucial to do. This training activity is carried out using the learning-by-doing method. This method was chosen because the training activities were carried out in a guided manner. Based on the training activities  two results can be obtained. First, the training related to the BeDiL learning media has been carried out smoothly. Second, participants can make BeDiL learning media in the form of posters that can be classified into two, namely complete BeDiL posters and incomplete BeDiL posters.